KOLIZYJNOPRAWNA PROBLEMATYKA MAŁŻEŃSKICH STOSUNKÓW MAJĄTKOWYCH W ŚWIETLE PRZEPISÓW NOWEJ USTAWY O P.P.M. Z 2011 R. - Żarnowiec, Łukasz (Zeszyty Prawnicze, 2016)
Conflict of Legal Issues Regarding Matrimonial Property Regimes under the New Private International Law of 2011 Summary The conflict-of-law method for the determination of the law applicable to matrimonial property regimes under the Polish International Private Law Act of 1965 became obsolete and no longer came up to current standards and needs, and therefore required thorough revision. The most important shortfalls of the previous regulation were the exclusion of freedom of choice of the law applicable to matrimonial property relations, the selection of criteria recognised as objective connecting factors, the excessive privilege of lex fori, and the lack of instruments protecting third parties entering into legal relations with a married couple. Amendments in the above-mentioned scope were introduced by the International Private Law Act of February 4, 2011 (Ustawa z dnia 4 lutego 2011 r. – Prawo prywatne międzynarodowe), that came into force on May 16, 2011. However, certain provisions of the new Act have raised doubts. This paper presents them and tries to provide a critical assessment.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />